2014
DOI: 10.1016/j.appet.2014.06.108
|View full text |Cite
|
Sign up to set email alerts
|

Weight stigma is stressful. A review of evidence for the Cyclic Obesity/Weight-Based Stigma model

Abstract: A B S T R A C TWeight stigma is highly pervasive, but its consequences are understudied. This review draws from theory in social psychology, health psychology, and neuroendocrinology to construct an original, generative model called the cyclic obesity/weight-based stigma (COBWEBS) model. This model characterizes weight stigma as a "vicious cycle" -a positive feedback loop wherein weight stigma begets weight gain. This happens through increased eating behavior and increased cortisol secretion governed by behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
495
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 519 publications
(531 citation statements)
references
References 97 publications
17
495
1
18
Order By: Relevance
“…Cross‐sectional studies in adolescent and adult populations lend some support to this, as they show that accurately identifying one's own weight status as being ‘overweight’, as opposed to failing to identify oneself as overweight, is associated with a range of poor mental health outcomes, including greater risk of depression 117, 118, 119 and reduced quality of life 120. A number of theoretical models also suggest that the psychological burden of identifying as ‘overweight’ could manifest itself in unhealthy behaviours that end up promoting weight gain and exacerbating obesity 121, 122, 123. In support of this, across three large nationally representative samples of the US and UK adults, individuals who identified that they were overweight went on to gain more weight than those who did not identify that they were overweight 124.…”
Section: Public Health Implications Of the Under‐detection Of Overweimentioning
confidence: 99%
“…Cross‐sectional studies in adolescent and adult populations lend some support to this, as they show that accurately identifying one's own weight status as being ‘overweight’, as opposed to failing to identify oneself as overweight, is associated with a range of poor mental health outcomes, including greater risk of depression 117, 118, 119 and reduced quality of life 120. A number of theoretical models also suggest that the psychological burden of identifying as ‘overweight’ could manifest itself in unhealthy behaviours that end up promoting weight gain and exacerbating obesity 121, 122, 123. In support of this, across three large nationally representative samples of the US and UK adults, individuals who identified that they were overweight went on to gain more weight than those who did not identify that they were overweight 124.…”
Section: Public Health Implications Of the Under‐detection Of Overweimentioning
confidence: 99%
“…Weight-based discrimination has been conceptualized as a 'social-evaluative' threat with likely downstream physiological as well as psychological effects (Dickerson & Kemeny, 2004;Tomiyama, 2014). Prior research on racial and health inequalities, for example, has documented the physiological impact of social denigration; such stress can activate the PERCEIVED WEIGHT AND HEALTH 5 sympathetic nervous system and induce sustained neuroendorcrine responses with potential deleterious health consequences (Daly, Boyce, & Wood, 2015;Williams & Mohammed, 2009).…”
Section: Perceived Weight and Healthmentioning
confidence: 99%
“…The effect was most strongly manifested by participants with higher BMIs (paralleling a nonsignificant trend obtained in Study 1). This in-group derogation has emerged in other weight stigma studies 17,18 and in this investigation was driven primarily by higher BMI participants elevating their ratings of thin-paired scents relative to heavy-paired scents. Unlike Study 1, the distractor object scent ratings did not differ from that of either weight image group.…”
Section: Resultsmentioning
confidence: 79%